PENGARUH RASIO PEMBAYARAN DIVIDEN DAN PENGELUARAN MODAL TERHADAP EARNINGS RESPONSE COEFFICIENTS (ERC) DENGAN ARUS KAS BEBAS SEBAGAI VARIABEL PEMODERASI - Galuh Aprilianti Putri, 10.05.51.0148 (Students Journal of Economic and Management, 2014)
This study examines the effect of dividend payout ratios and capital expenditures on earnings response coefficients with free cash flow as amoderating variable. Economic decision made by market participants based on information derived from the financial statements are usually reflected in the market reaction. Response or reaction to information market accounting profit is seen from the sensitivity of the stock price change is called the Earnings Response Coefficients (ERC). Factors affecting the ERC include : Dividend Payout Ratio (DPR) and capital expenditures. This research was conductedat the companies listed in Indonesia Stock Exchange the period 2009-2011. The purpose of this study was to analyze the effect of Dividend Payout Ratio (DPR) and Capital expenditures on Earnings Response Coefficients (ERC) and to analyze the moderating effect of Free Cash Flow (FCF).The sample used in this study were12 manufacturing company data dividends for 3 years. The data used are secondary data. The analysis technique used is moderated regression analysis. According to analysis done canbe seenthat the House of Representatives and capitl expenditure has no effect on the ERC, FCF moderating variables influence the parliament to ERC but not moderate the effect of variable capital expenditure on CAR. According to analysis done can be seen that the House of Representatives and capital expenditure has no effect on the ERC, FCF moderating variables influence the Parliament to ERC but not moderate the effect of variable capital expenditure on CAR. Key words : Dividend Payout Ratio, Capital Expenditure, Free Cash Flow, Earnings Response Coefficients.